Hirschman and Furtado's contributions for a historical discussion on regional economic resilience to droughts in the Brazilian semiarid: an evolutionary approach - Tupy, Igor Santos; Silva, Fernanda Faria (Cadernos do Desenvolvimento, 2019)
This paper aims to analyze the economic resilience of Brazil’s semiarid region to the phenomenon of droughts in the first half of the 20th century. Specifically, it uses Hirschman and Furtado’s analyses of economic development and the question of droughts in the Brazilian Northeast to establish the notion of resilience to droughts from an evolutionary perspective. The paper highlights certain political and institutional aspects as determinants of regional resilience by studying the evolution of government-backed initiatives to cope with such droughts. It also shows how this particular economy has become vulnerable and susceptible, limited in its ability to learn from or adapt to such shocks, thereby effectively lacking any resilience to droughts.